2007
DOI: 10.1111/j.1478-3231.2007.01558.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in patients with chronic hepatitis B

Abstract: CH-B patients have better HRQL than CH-C, PBC and population norms. CH-B patients' overall utility scores are lower than population norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 38 publications
5
62
4
2
Order By: Relevance
“…Our results differ from literature data [14]. According to the most relevant studies, generic QoL score (mainly assessed by SF-36 questionnaire) was significantly lower within the patients with CLD compared with healthy controls, including the studies of Bondini et al [20], which indicate significantly lower SF-36 scores in patients with cholestatic liver diseases and viral hepatitis C in comparison with the control group. The study of Younossi et al [21] pointed out that the SF36 scores were significantly lower in the group of patients with CLD regardless of the etiology, compared with healthy subjects.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Our results differ from literature data [14]. According to the most relevant studies, generic QoL score (mainly assessed by SF-36 questionnaire) was significantly lower within the patients with CLD compared with healthy controls, including the studies of Bondini et al [20], which indicate significantly lower SF-36 scores in patients with cholestatic liver diseases and viral hepatitis C in comparison with the control group. The study of Younossi et al [21] pointed out that the SF36 scores were significantly lower in the group of patients with CLD regardless of the etiology, compared with healthy subjects.…”
Section: Discussioncontrasting
confidence: 57%
“…Ranking within groups is presented in Table 1. 3,6,21,23,27), the activity (3 questions; the order of 7, 9, 14), emotional functioning (8 questions; the order of 10,12,15,16,19,20,24,26), as well as concerns (5 questions; the order of 18,22,25,28,29). The average score for each domain is equal to the sum of ranks for all issues related to this area, divided by the number of questions.…”
Section: Methodsmentioning
confidence: 99%
“…Strengths of the study include its large size and high response rate, and also use of an instrument that has been extensively validated in diverse populations of healthy and chronically ill individuals (17,25,(33)(34)(35). This report includes a greater number of respondents and a higher response rate than any other available report of HRQOL following RRT in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Those who died during the course of the study were assigned an HUI3 score of 0 at the cycle of their death and censored thereafter. There is substantial evidence on the construct validity of HUI3 in population health and clinical studies, including studies of people with chronic conditions that are associated with alcohol consumption (liver disease, type 2 diabetes, dementia, impaired mental health, and heart disease) (Asakawa et al, 2008;Bondini et al, 2007;Feeny et al, 2009Feeny et al, , 2012Fisk et al, 2005;Garster et al, 2009;Grootendorst et al, 2000;Jones et al, 2005;Kavirajan et al, 2009;Maddigan et al, 2004Maddigan et al, , 2006Marra et al, 2005;Revicki et al, 2008;Wilkins, 2006;Younossi et al, 2001), and the scoring procedures can be found elsewhere (Feeny et al, 2002. Differences (or changes) of .03 or more in the overall HUI3 score are important clinically (Drummond, 2001;Grootendorst et al, 2000;Horsman et al, 2003).…”
Section: Methodsmentioning
confidence: 99%